Quando o monstro convoca a resistência biopolítica: estratégias comunicativas na arte e na vida - Souza, Virgínia Laís de (2017)
The subject of this thesis is the monstrous body. This topic has been addressed by authors such as Jean-Jacques Courtine (2013; 2008), who explored the difficulties faced by human beings coping with (so-called) abnormal body types. However, the main goal of the present work is to analyse how a monstrous body can lead the individual to other forms of existence, over and above the stigmas that frequently paralyse the self. Based on the discussions taken up by Antonio Negri (2007, 2003) and Barbara Szaniecki (2014), the monster and the singular characteristics of monstrosity can be viewed as triggers for political and communicational processes and not merely as physical bodies which are socially excluded. In this sense, the monstrous body can be seen as a corpusmedia constituted from its co-evolutionary relations with the environment. The main hypothesis of this thesis is that artistic creations have contributed at a fundamental level to recent changes in our understanding of the monstrous body, undercutting recurrent interpretations that placed monstrous bodies solely within the scope of the exotic and led to their consistent marginalisation as an object of study. It is not merely a question of integrating a stigmatised body into society, but of analysing the power of art to reveal alternatives to our preconceptions of how to look at and represent a body that has been excluded from society. The empirical corpus of this research is derived through dance and theatrical presentations performed mainly in the 2000s, whose performers ranged from backgrounds as immigrants, foreigners and individuals of African descent to artists with physical disabilities. Among these presentations are included works by choreographers such as Jérôme Bel, Claire Cunningham, Faustin Linyekula and the theatre companies Theater Hora and Back to Back. The relevance of this thesis lies in demonstrating how these bodies can subvert stereotypes which have been rooted for centuries in social discourse and media. This work also seeks to highlight the construction of discursive practices that recognise monstrosity when compared to normal standards but which are not confined to pre-conceived interpretations, leading to new patterns of subjective analysis